The history of US-Japan relations from Perry to the present - Iokibe, Makoto 1943-; Minohara, Toshihiro 1971- (Palgrave Macmillan, 2017)
"This is wonderful book that provides a fresh perspective into the current state of US-Japan relations by placing it within the greater historical context of nearly two centuries of political and diplomatic interactions between the two nations across the Pacific."--Akio Watanabe, Professor Emeritus, the University of Tokyo, Japan.